Psychology of the relationships in the dentist’s practice (Эндодонтия Today)
In the modern world there is a tendency of an integrated approach to solving dental problems with the active involvement and use of the latest achievements of psychology, sociology, behavioral sciences. A study conducted at the of pediatric dentist’s office with the use of psychological techniques revealed the increased emotional experience and anxiety in young children. The gender differences in the experience of children visiting the dentist were established. It is proved that in providing dental care for children clinicians need to be skilled in psychological approach to each child. In preparing the child to visiting the dentist the close cooperation of doctor, psychologist and parents is required